Asset inspection for project integrity a reference guide for executing and or implementing agencies. (Metro Manila, Philippines Asian Development Bank, 2018)
This guide helps to identify integrity risks and verify that project funds are used for their intended purposes and beneficiaries. It provides checklists on the preparation and inspection of goods and works, what to look out for, and the types of inspected project outputs.
Keywords: Public administration -- ADB; Electronic books